Peningkatan Kompetensi Self-Help Konseling Realita Berbasis Online - M Ramli; Nur Hidayah; Nur Mega Aris Saputra; Husni Hanafi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
The problems faced by students are currently increasingly complex with the uncontrollable developments of the times and the impact caused by the co-19 pandemic. One solution that can be applied is the use of self-help online reality counseling to help overcome student problems, however, counselors have low competence in the development and application of self-help online reality counseling. Low competence both in terms of understanding and application is shown by service partners who have never implemented self-help-based counseling services for students. Therefore, the implementation of this service provides training in the application of self-help online-based reality counseling to counselors in Malang Raya. The training activity took place in the D3 FIP UM hall with the Malang Raya High School MGBK partner. The results of training on the application of self-help online reality counseling show that in terms of understanding, counselors experience a change from low to moderate to high. Counselors have the ability of counselors to design and use online reality counseling self-help applications.